Assessment of Traditional Rice Beer Quality Manufactured by Different Ethnic Tribes of Assam, India - S. Goswami, Bijoy; Borgohain, Purnima; Updhya, Puja; Barthakur, Manoj (Asian Journal of Chemistry, 2020)
Ethnic communities of North-East India consume various traditional beverages which are mostly prepared by fermentation of rice of their own. Many ethnic communities reside in Assam, India and the consumption of fermented drinks is always considered to be their culture and existence of the ethnic tribes. In present work, eight different rice beer samples are collected from different parts of Assam representing Ahom, Mising and Karbi community. The samples are characterized with respect to various physico-chemical analysis and microbiological parameters. In present work, the methodologies for the process of preparation of rice beers by different ethnic communities are also carefully observed and properly documented. It has been observed that all the samples are acidic in nature and the pH values are ranged from 2.83-5.05, while conductance ranged from 0.028-1.86 ms/cm. The amount of free carbon dioxide varies from 0.105 g/L to 6.81g/L. The amount of hardness varied from 0.012 g/L to 0.38 g/L. The sugar content of various rice beers ranged from below detection limit (BDL) to 4.4 g/100 mL while the percentage of ethanol varies from 2.2 to 5.7 g/100 mL. The correlation matrix study also shows a good positive correlation between conductance and TDS, hardness, free CO2 and bicarbonate alkalinity. In this study, no coliform bacterial contamination appeared while the colony forming unit ranged from 0.3 × 105 to 1.68 × 105 cfu mL-1.